Acute neurovascular events in cancer patients receiving anti-vascular endothelial growth factor agents: Clinical experience in Paris University Hospitals. (October 2016) - Tlemsani, Camille; Mir, Olivier; Psimaras, Dimitri; Vano, Yann-Alexandre; Ducreux, Michel; Escudier, Bernard; Rousseau, Benoit; Loirat, Delphine; Ceccaldi, Bernard; André, Thierry; Goldwasser, François; Ricard, Damien
Abstract: Background: Despite the increasing and broadening use of agents targeting the vascular endothelial growth factor (VEGF) pathway, little is known on their acute neurovascular toxicities. Methods: This retrospective, multi-centre study examined the characteristics of patients with solid tumours who experienced an ischaemic or haemorrhagic stroke, a transient ischaemic accident (TIA) or a posterior reversible encephalopathy syndrome (PRES) while under anti-VEGF and until 8 weeks after termination of treatment and evaluated their management in our institutions from 2004 to 2014. Patients with newly diagnosed or progressive cerebral metastases at the time of the acute neurovascular event were excluded. Results: Thirty-four patients (55.9% men) were identified, and experienced either ischaemic stroke (n = 18), PRES (n = 9), TIA (n = 6) or haemorrhagic stroke (n = 1). At initiation of anti-VEGF agents, 64.7% of patients had previous cardiovascular risk factors, and 52.9% had hypertension. Eight patients (23.5%) had received cerebral radiotherapy, five of which concomitantly to anti-VEGF treatment. Six (17%) patients died in the 8 weeks following the acute neurovascular event, and only 55.9% recovered their initial neurological status. Overall, 1-year and 2-year survival rates after the acute neurovascular event were 67.9% and 50%, respectively. When anti-VEGF agents were reintroduced (n = 6), severe vascular toxicity recurred in two patients. Conclusions: Neurovascular events under VEGF treatments are potentially severe, and the management of comorbid conditions has to be improved. A prospective collection of data and standardised management of such events is therefore being structured in our institutions. Highlights: Patients with neurovascular toxicities have mostly cardiovascular risk factors. These toxicities are severe: 50% of patients do not recover their neurological state. Management of toxicities is crucial: most patients are alive 2 years after the event. When anti-vascular endothelial growth factor agents are reintroduced, severe vascular toxicity could recur.